1998
DOI: 10.1007/s002130050793
|View full text |Cite
|
Sign up to set email alerts
|

Abuse liability of flunitrazepam among methadone-maintained patients

Abstract: Abuse liability and acute subjective and psychomotor effects of flunitrazepam were assessed in ten methadone-maintained males with history of benzodiazepine and alcohol use, who voluntarily participated in a double-blind, controlled, cross-over, randomized clinical trial. There were six experimental sessions in which a single oral dose of flunitrazepam 1, 2, and 4 mg; triazolam 0.5 and 0.75 mg; and placebo was given. Evaluations included physiological measures; psychomotor performance tasks (simple reaction ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 43 publications
4
28
0
2
Order By: Relevance
“…Furthermore, the 2-mg dose produced the greatest level of disruption in psychomotor performance (reaction time, balance, and digit symbol substitution). These results were replicated at 4 mg flunitrazepam vs placebo in methadone maintenance patients (Farre et al 1998). McKay and Dundee (1980) observed significant memory impairment with 1 mg flunitrazepam, whereas Jackson et al (1993) observed impaired reaction time but did not find significant effects on memory with 2 mg flunitrazepam.…”
mentioning
confidence: 66%
“…Furthermore, the 2-mg dose produced the greatest level of disruption in psychomotor performance (reaction time, balance, and digit symbol substitution). These results were replicated at 4 mg flunitrazepam vs placebo in methadone maintenance patients (Farre et al 1998). McKay and Dundee (1980) observed significant memory impairment with 1 mg flunitrazepam, whereas Jackson et al (1993) observed impaired reaction time but did not find significant effects on memory with 2 mg flunitrazepam.…”
mentioning
confidence: 66%
“…Oral administration of the freeze-dried material induced feelings of increased activation (ARCI-A, VAS-stimulated), euphoria and well being (ARCI-MBG, VAS-high, VAS-liking, VAS-good effects), and somatic effects (ARCI-LSD), in addition to perceptual modifications (HRS-Perception, VAS-visions) and changes in thought content (HRS-Cognition) and increased emotional lability (HRS-Affect). Increases in VAShigh have been observed after a great variety of drugs including MDMA , cocaine (Farré et al, 1993), and the sedative flunitrazepam (Farré et al, 1998). The VAS-stimulated item reflects more specifically the effects of psychostimulants such as amphetamine and MDMA .…”
Section: Discussionmentioning
confidence: 99%
“…The VAS-stimulated item reflects more specifically the effects of psychostimulants such as amphetamine and MDMA . Increases in VAS-drunken, which was the least modified VAS item by ayahuasca, have been observed mainly after sedatives, such as flunitrazepam (Farré et al, 1998), and alcohol (Farré et al, 1993), but also after 125 mg of MDMA . Regarding the HRS, our findings are in line with results by other researchers who have demonstrated statistically significant increases in all HRS jpet.aspetjournals.org scales after the administration of various psychedelics, such as i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzodiazepine use is strongly linked to a range of negative consequences, including poorer adherence to maintenance programs [24,25] , greater psychological distress, more HIV risk-taking behaviors, poorer health and social functioning, and an increased incidence of overdosing and mortality [26,27] . Several studies have highlighted the potential for these drugs to have additive effects when taken together, including increased sedation and respiratory depression, even at therapeutic doses of each drug [28][29][30] . The risks posed by concomitant benzodiazepine use may vary according to the maintenance drug used.…”
Section: Capacity Of Gpsmentioning
confidence: 99%